2014
DOI: 10.1371/journal.pone.0087140
|View full text |Cite
|
Sign up to set email alerts
|

Tempol, an Intracellular Antioxidant, Inhibits Tissue Factor Expression, Attenuates Dendritic Cell Function, and Is Partially Protective in a Murine Model of Cerebral Malaria

Abstract: BackgroundThe role of intracellular radical oxygen species (ROS) in pathogenesis of cerebral malaria (CM) remains incompletely understood.Methods and FindingsWe undertook testing Tempol—a superoxide dismutase (SOD) mimetic and pleiotropic intracellular antioxidant—in cells relevant to malaria pathogenesis in the context of coagulation and inflammation. Tempol was also tested in a murine model of CM induced by Plasmodium berghei Anka infection. Tempol was found to prevent transcription and functional expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 139 publications
(219 reference statements)
1
30
0
Order By: Relevance
“…To address whether this dynamic expression of surface markers was confounding our interpretation of which monocyte subset expresses TF in response to LPS, we sorted the three major monocyte subsets based on the dichotomous surface expression of CD14 and CD16 (CD14 ++ CD16 - , CD14 + CD16 + and CD14 dim CD16 + ), stimulated each subset with LPS and then examined TF expression in cell lysates and measured TF functional activity by a colorimetric assay which quantifies the formation of the coagulation factor Xa (27) (Figure 1E). In unstimulated conditions, TF protein expression and functional activity by each monocyte subset was uniformly low in cultures (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…To address whether this dynamic expression of surface markers was confounding our interpretation of which monocyte subset expresses TF in response to LPS, we sorted the three major monocyte subsets based on the dichotomous surface expression of CD14 and CD16 (CD14 ++ CD16 - , CD14 + CD16 + and CD14 dim CD16 + ), stimulated each subset with LPS and then examined TF expression in cell lysates and measured TF functional activity by a colorimetric assay which quantifies the formation of the coagulation factor Xa (27) (Figure 1E). In unstimulated conditions, TF protein expression and functional activity by each monocyte subset was uniformly low in cultures (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Tempol (Tmp) is a SOD-mimetic drug that efficiently neutralizes ROS [43]. These drugs were administered daily by gavage.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, we next tested TPL, an SOD mimetic that has been shown to cross biological membranes (39) and effectively scavenge superoxide (5558). A recent study in experimental cerebral malaria showed TPL slightly increased survival in treated mice (59). Similar to that model, i.p.…”
Section: Discussionmentioning
confidence: 99%